Restricting IEC 61131-3 programming languages for use on high integrity applications - Mário de Sousa (2008)
When developing applications with high integrity requirements, the choice of programming language is of utmost importance. In fact, IEC 61508 includes a table with suggested programming languages for each SIL (Safety Integrity Level). The languages defined in IEC 61131-3 are included in this table, but are only highly recommended for the higher SILs if a subset of the languages are used. In this paper we propose restrictions and changes to the IEC 61131-3 languages that constitute a subset of the languages with the objective of making them appropriate for the development of high integrity applications.